2003
DOI: 10.1038/sj.bjp.0705273
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of nitric oxide and tachykinins in the effects induced by protease‐activated receptors in rat colon longitudinal muscle

Abstract: 1 The aim of the present study was to verify a possible involvement of nitric oxide (NO) and of tachykinins in the contractile and relaxant effects caused by the activation of protease-activated receptor (PAR)-1 and PAR-2 in the longitudinal muscle of rat colon. 2 Mechanical responses to the PAR-1 activating peptides, SFLLRN-NH 2 (10 nM -10 mM) and TFLLR-NH 2 (10 nM -10 mM), and to the PAR-2-activating peptide, SLIGRL-NH 2 (10 nM -10 mM), were examined in vitro in the absence and in the presence of different a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 48 publications
(48 reference statements)
1
27
1
Order By: Relevance
“…POSTINFECTIOUS PAR-2-ASSOCIATED INTESTINAL DYSFUNCTION the participation of specific neurotransmitters in the different phases of PAR-2-mediated responses, as previously described in the rat colon (25). Further studies are needed to characterize the underlying mechanisms generating PAR-2-mediated biphasic secretory and motor responses in the jejunum.…”
Section: G397mentioning
confidence: 79%
See 1 more Smart Citation
“…POSTINFECTIOUS PAR-2-ASSOCIATED INTESTINAL DYSFUNCTION the participation of specific neurotransmitters in the different phases of PAR-2-mediated responses, as previously described in the rat colon (25). Further studies are needed to characterize the underlying mechanisms generating PAR-2-mediated biphasic secretory and motor responses in the jejunum.…”
Section: G397mentioning
confidence: 79%
“…Therefore, it is feasible that PAR-2-mediated increased motility and luminal secretion would contribute to a "protective" response, controlling penetration and interaction of luminal antigens with the epithelium and bacterial overgrowth in physiological conditions (3,27). In addition, these PAR-2-mediated defensive responses are apparently induced by direct effects on the epithelium and the muscle, as the modulation of secretion and motility by SLIGRL-NH 2 was TTX independent (25,26,47). Nevertheless, we cannot rule out …”
Section: G396mentioning
confidence: 99%
“…In addition, local mast cell degranulation may have induced motility changes [11]. Mule et al [29, 50] have shown that activation of protease-activated receptors (PAR) can cause colon smooth muscle relaxation as well as contraction. PAR agonists such as mast cell-derived tryptase may have caused PAR activation in both casein- and whey-sensitized mice.…”
Section: Discussionmentioning
confidence: 99%
“…5). In intestinal smooth muscle, PAR-2 agonist induces relaxation by the activation of small conductance Ca 2+ -activated K + -channel opened with the influx of extracellular Ca 2+ through L-type voltage-dependent channels [19,26], by the production of NO [18] or by the activation of enteric inhibitory neurons [16]. Under inflammatory conditions, the activity of smooth muscle L-type Ca 2+ channels is suppressed [1,13,28], the cGMP-relaxation pathway is damaged [31] and non-adrenergic non-cholinergic nerves are impaired [17].…”
Section: Discussionmentioning
confidence: 99%